Object-oriented JavaScript : learn everything you need to know about object-oriented JavaScript with this comprehensive guide, enter the world of cutting-edge development! - Antani, Ved (Packt, 2017)
Learn everything you need to know about object-oriented JavaScript with this comprehensive guide. Enter the world of cutting-edge development! About This Book This book has been updated to cover all the new object-oriented features introduced in ECMAScript 6 It makes object-oriented programming accessible and understandable to web developers Write better and more maintainable JavaScript code while exploring interactive examples that can be used in your own scripts Who This Book Is For This book is ideal for new to intermediate JavaScript developers who want to prepare themselves for web development problems solved by object-oriented JavaScript! What You Will Learn Apply the basics of object-oriented programming in the JavaScript environment Use a JavaScript Console with complete mastery Make your programs cleaner, faster, and compatible with other programs and libraries Get familiar with Iterators and Generators, the new features added in ES6 Find out about ECMAScript 6's Arrow functions, and make them your own Understand objects in Google Chrome developer tools and how to use them Use a mix of prototypal inheritance and copying properties in your workflow Apply reactive programming techniques while coding in JavaScript In Detail JavaScript is an object-oriented programming language that is used for website development. Web pages developed today currently follow a paradigm that has three clearly distinguishable parts: content (HTML), presentation (CSS), and behavior (JavaScript). JavaScript is one important pillar in this paradigm, and is responsible for the running of the web pages. This book will take your JavaScript skills to a new level of sophistication and get you prepared for your journey through professional web development. Updated for ES6, this book covers everything you will need to unleash the power of object-oriented programming in JavaScript while building professional web applications. The book begins with the basics of object-oriented programming in JavaScript and then gradually progresses to cover functions, objects, and prototypes, and how these concepts can be used to make your programs cleaner, more maintainable, faster, and compatible with other programs/libraries. By the end of the book, you will have learned how to incorporate object-oriented programming in your web development workflow to build professional JavaScript applications. Style and approach Filled with practical instructions, the book shows you how to implemen...
Includes index.
Keywords: JavaScript (Computer program language); Object-oriented programming (Computer science); Computer software.; Computer programs.; elektronické knihy; electronic books